Aesthetic relevance of Beksan Menak Sudarawerti Sertupelaeli to wards character education - Enis Niken Herawati; Sri Rochana Widyastutieningrum; RM. Pramutomo RM. Pramutomo; Slamet Slamet (LPMPP Universitas Negeri Yogyakarta, 2023)
Beksan Menak Sudarawreti Sirtupelaeli, a show that is originally from the Javanese Palace. This dance is Yasan Dalem or the creation of Sri Sultan Hamengkubuwono IX. Its unique character lies in its movements. Revitalization of Estetik Beksan Menak Sudarawreti Sirtupelaeli to develop character education is done by qualitative methods, namely by describing the Aesthetic Revitalization of Beksan Menak Sudarawreti Sirtupelaeli to Develop Character Education in detail. The study used primary and secondary data sources. The primary data source is the interview record. The researcher's secondary data sources were obtained through literature studies in the form of books, scientific journals that support research, and photo documentation of dance movement variations, Sudarawreti Sirtupelaeli kostrum. Data collection techniques are carried out with observation, interview, document study and literacy techniques. Understanding and knowing the aesthetics in the movement of Beksan Menak Sudarawreti Sirtupelaeli and knowing its relevance to character education is the purpose of this research. Based on the analysis of the data conducted, it was concluded that in the movement of Beksan Menak Sudarawreti Sirtupelaeli there are aesthetic values that contain meanings that are in accordance with the values of character education. Beksan Menak Sudarawreti Sirtupelaeli also has a relationship with the context of art and education as a guideline for daily life or values that contain noble ethics that are worth knowing.